2019
DOI: 10.1007/s11042-019-7250-z
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy logic approach to reliable real-time recognition of facial emotions

Abstract: This paper represents our newly developed software for emotion recognition from facial expressions. Besides allowing emotion recognition from image files and recorded video files, it uses webcam data to provide real-time, continuous, and unobtrusive facial emotional expressions. It uses FURIA algorithm for unordered fuzzy rule induction to offer timely and appropriate feedback based on learners' facial expressions. The main objective of this study was first to validate the use of webcam data for a real-time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 66 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…Kiavash Bahreini, Wim Van der Vegt and Wim Westera offers high quality, reliable recognition, and categorisation of emotions use by fuzzylogic based emotion recognition. This study achieves an 83.2% average accuracy which showed that most intensive emotions (e.g., happiness, surprise) can be detected better than the remainder emotions except neutral and fear [24].…”
Section: Related Workmentioning
confidence: 71%
“…Kiavash Bahreini, Wim Van der Vegt and Wim Westera offers high quality, reliable recognition, and categorisation of emotions use by fuzzylogic based emotion recognition. This study achieves an 83.2% average accuracy which showed that most intensive emotions (e.g., happiness, surprise) can be detected better than the remainder emotions except neutral and fear [24].…”
Section: Related Workmentioning
confidence: 71%
“…Emotion-related data are also saved in the same database (heart-rate values or emotions, in the case of non-VR use of the system). For detecting emotions through the facial expressions captured by the webcam, we used the RAGE (Realising an Applied Gaming “Emotion Detection Asset” created by the Open University of the Netherlands [ 81 ] which is capable of identifying the six basic emotions: happiness, sadness, surprise, fear, disgust, and anger [ 82 ] or if the user is having a neutral expression.…”
Section: Our Systemmentioning
confidence: 99%
“…Cho et al [52] measured human stress using a respiration variability spectrogram (RVS), which was measured with a thermal imaging camera using CNN. In addition to the machine learning and deep learning mentioned above, many studies have been conducted to analyze emotions using fuzzy theory [25,53,54]. Aside from that, deep learning is used in various fields [55].…”
Section: Emotion Classification Using Machine Learning and Deep Learningmentioning
confidence: 99%